DYNAMIC TRENDS OF WAGE IN UKRAINE: PROSPECTS OF EUROPEAN INTEGRATION - Ganna KATARANCHUK (USV Annals of Economics and Public Administration, 2016)
We analyze the main trends of the national economy and the dynamics of wages in Ukraine and other postsocialist countries in terms of the prospects of Ukraine's integration into the European economic and social space. The estimation of the impact of the wage indices for the welfare of citizens. The basic factors of Ukraine’s backlog in terms of wages from other countries and the possibilities and prospects of solving this problem are determined